2018
DOI: 10.1002/jbio.201800219
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic graphene quantum dot as a dual‐modality contrast agent for confocal fluorescence microscopy and magnetomotive optical coherence tomography

Abstract: A magnetic graphene quantum dot (MGQD) nanoparticle, synthesized by hydrothermally reducing and cutting graphene oxide-iron oxide sheet, was demonstrated to possess the capabilities of simultaneous confocal fluorescence and magnetomotive optical coherence tomography (MMOCT) imaging. This MGQD shows low toxicity, significant tunable blue fluorescence and superparamagnetism, which can thus be used as a dual-modality contrast agent for confocal fluorescence microscopy (CFM) and MMOCT. The feasibility of applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In contrast to Fl/MRI, Li et al reported on superparamagnetic GQDs (MGQDs) as a dual-modal contrast agent for Fl/optical coherence tomography imaging (Fl/OCT) (Li et al, 2019). The MGQDs internalized into 3T3 exhibited blue fluorescence as revealed by in vitro CLSM imaging (Figure 14A), while for OCT, the MGQD-labeled cells were placed on an agar gel to mimic the human soft tissues, and then imaged by an in-house magnetomotive OCT system.…”
Section: Dual-modal Imagingmentioning
confidence: 99%
“…In contrast to Fl/MRI, Li et al reported on superparamagnetic GQDs (MGQDs) as a dual-modal contrast agent for Fl/optical coherence tomography imaging (Fl/OCT) (Li et al, 2019). The MGQDs internalized into 3T3 exhibited blue fluorescence as revealed by in vitro CLSM imaging (Figure 14A), while for OCT, the MGQD-labeled cells were placed on an agar gel to mimic the human soft tissues, and then imaged by an in-house magnetomotive OCT system.…”
Section: Dual-modal Imagingmentioning
confidence: 99%
“…Another advantage of MM-OCT is that it can use MRI contrast agents, in which SPIONs have been approved by FDA. The development of novel magnetomotive contrast agents is relatively easy [ 98 , 99 , 100 ]. Besides, many synthesized magnetic microspheres have been developed as efficient contrast agents for multiple imaging modalities, for instance, MM-OCT and fluorescence [ 101 ].…”
Section: Magnetomotive Oct and Its Applicationsmentioning
confidence: 99%